The Effect of Transformational Leadership And Organizational Support On Turnover Intention Mediated With Organizational Commitment At Prima In Hotel Malioboro - Aisyah Rahmawati; Didik Subiyanto; Tri Ratna Purnamarini (Journal of Economy, Accounting and Management Science (JEAMS), 2025)
This study aims to determine the effect of transformational leadership and organizational support on turnover intention mediated by organizational commitment at Prima In Hotel Malioboro Yogyakarta. This type of research is quantitative. The population in this study were 60 employees of Prima In Hotel Malioboro Yogyakarta using the sampling technique used in this study using saturated sampling technique. Data quality test analysis using classical assumption tests, normality tests, multicollinearity tests, and heteroscedasticity tests. Multiple linear regression analysis test. Hypothesis testing using f test, t test, coefficient of determination () test, and sobel test. Based on the results of the research test, it shows that transformational leadership has a negative and insignificant effect on turnover intention, organizational support has a negative and insignificant effect on turnover intention, transformational leadership and organizational support have a negative and insignificant effect on turnover intention. Organizational commitment has a positive and significant effect on turnover intention.